ANTIOXIDANT POTENTIAL OF BIOACTIVE COMPOUNDS IN ETHANOL EXTRACTS OF SEAGRASS AND MACROALGAE FROM LAMPUNG WATERS - Ainun Rohmawati Bareta; Endang Linirin Widiastuti; Nuning Nurcahyani; Riris Roiska; Yusyam Leni (Universitas Mataram, 2025)
The sea in Indonesia covers 75% of its total land area. According to data from the Ministry of Marine Affairs and Fisheries (2019), Indonesia has approximately 5.8 million km² of water area out of a total territory of 7.81 million km². The biodiversity in Indonesia's coastal areas is utilized by coastal communities in their daily lives. Coastal resources also have potential in the health sector, such as seagrass, macroalgae, and taurine, which can be used as raw materials for natural medicine. The purpose of this study is to analyze the antioxidant potential based on the IC50 value of taurine, ethanol extracts of the seagrasses Enhalus acoroides and Cymodocea rotundata, as well as the macroalgae Padina australis and Sargassum duplicatum. The method used is the antioxidant activity assay using DPPH (2,2-Diphenyl-1-picrylhydrazyl). The results of this study indicate that, after testing with DPPH, only the ethanol extract of Cymodocea rotundata had an IC50 value of < 200 µg/mL, specifically -652.95 µg/mL, whereas the IC50 values of taurine, the ethanol extract of Enhalus acoroides, and the ethanol extracts of the macroalgae Padina australis and Sargassum duplicatum were > 200 µg/mL, indicating no antioxidant activity. In conclusion, only the ethanol extract of Cymodocea rotundata has the potential to be a candidate for antioxidant raw material.